IMPORTANCE OF INTERPERSONAL RELATIONSHIP IN STEVEN SODERBERGH'S ERIN BROCKOVICH (2000): A HUMANISTICPSYCHOLOGICAL CRITICISM - KARTIKASARI, DIANITA (2011)
The major problem of this research is to reveal how the importance of interpersonal relationship is reflected in Erin Brockovich movie directed by Steven Soderbergh. The objectives of the research are to analyze the movie based on its structural elements and humanistic psychological criticism. In analyzing the movie, the researcher uses qualitative research. There are two kinds of data source, namely primary and secondary data sources. The primary data is Erin Brockovich movie which forms texts and images, the secondary data is any literature related to this research. The writer collects the data from both primary and secondary data sources by note taking and image capturing and also using library research. The technique of data analysis is descriptive technique. The results of the research are as follows. Firstly, the structural elements of Erin Brockovich movie build good production; the director wants to deliver the message through the character Erin Brockovich. Interpersonal relationship is key to success in career. Secondly, from humanistic psychological criticism, one of characters's self actualization is interpersonal relationship that is influenced by three aspects; communication, self disclosure, acceptance. Steven Soderbergh reflects phenomenon of humanistic psychological that is a woman who has motivation to help other people based on her experiences.